A rapid and economical sample pretreatment method using molecularly imprinted polymers for bioavailable content analyses of oxytetracycline in soils. Issue 4 (20th April 2020) - Cui, Shiyao; Cao, Haiyan; Wang, Yixiang; Su, Yuhong
Abstract: In order to analyze the bioavailable oxytetracycline (OTC) contents of soils, a new high-efficiency and economical pretreatment method was established using a molecularly imprinted polymer (MIP) with high affinity and specific selectivity for OTC synthesized by bulk polymerization. For comparison, an Oasis HLB solid phase extraction (SPE) method was used to measure the total extractable OTC content of soils. The resulting OTC recoveries from the spiked soil solutions using the MIP method ranged from 80.78±.26% to 93.75 ± 6.79%, with an average of 86.00 ± 2.13%, and a relative standard deviation of 2.48% ( n = 5), when OTC concentrations in spiked soil solutions varied from 0.5 to 100.0 μg L −1 . When OTC contents in spiked soils varied from 1.0 to 500.0 μg kg −1 and soils were aged for three weeks, OTC recoveries from spiked soils with the Oasis HLB SPE method ranged from 78.16 ± 3.72% to 96.67 ± 1.62% ( n = 3), while those with the MIP method ranged from 57.43 ± 3.48% to 76.34 ± 1.30% ( n = 3). Analyses of OTC contents in five soil samples indicated that bioavailable OTC contents were only 1.35%–5.87% of the total soil OTC contents. Data from the new method were more valuable than the Oasis HLB SPE method on OTC pollution intensity assessment, potential ecological, and environmental risks evaluation.